An Analytical Study of the Nonsinglet Spin Structure Function g1NS(x,t) Up to NLO in the DGLAP Approach at Small x - Neelakshi N. K. Borah; D. K. Choudhury (Advances in High Energy Physics)
A next-to-leading order QCD calculation of nonsinglet spin structure function g1NS(x,t) at small x is presented using the analytical methods: Lagrange’s method and method of characteristics. The compatibility of these analytical approaches is tested by comparing the analytical solutions with the available polarized global fits.